Extraction, Characterization and Antibacterial Activity of Chitosan from Mud Crab Scylla serrata - Alagiri, Anju; Parthiban, Janani; Ashok, Anjana; Velayutham, Meiyalagan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The shellfish waste accumulated on a huge scale at seashores and in the seafood industry and very low quantities were used to extract chitosan. In this study, chitosan was extracted from the mud crab Scylla serrata shell using conventional chemical methods. The extracted chitosan and commercial chitosan were verified through Field Emission Scanning Electron Microscopy (FE-SEM), Attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), X-ray diffraction (XRD), and an elemental analyzer. ATR-FTIR spectrum confirmed the presence of characteristics compounds of chitosan and XRD patterns exhibited crystallinity of chitosan having centered peaks at 10º and 20º in 2θ. Moreover, 46.24% of the degree of deacetylation was obtained for the extracted chitosan altogether enhancing the quality of extracted chitosan. In addition to this, the extracted chitosan was tested for its antibacterial activity against two Gram-negative (E. coli and Pseudomonas) and two Gram-positive bacteria (Staphylococcus and Bacillus) in vitro. The antimicrobial activity of extracted chitosan was evident with the greater zone of inhibition against E. coli (26±0.32mm) and the least against Staphylococcus (18mm). Hence the present study gives insight into the biological properties of extracted chitosan from Scylla serrata thereby paving the way for its further use in biomedical science and microbiology.